Geographic Views on the Nepali Newspaper: An Analysis on Press Prints and Universal Understanding - Panday, Ram Kumar (The Third Pole: Journal of Geography Education, 2009)
The profession of newspaper has been becoming more challenging in recent years. In the underdeveloped country like Nepal, media has been misused, misguided and misbehaved. The big publishing house monopolized market. They have influenced in using government facilities and diverting people's attention towards their narrow interest of political nature. In fact, newspaper can play disaster role to destroy political and social system. In the time of people's movement, newspaper has played active role to initiate revolution. Negative news has been diffused much during the People's Movement. Everything good or bad has been criticized. Newspapers often used bombarding words to oppose opposition's role. Similarly, unsocial and inhuman activities have been encouraged by publishing random thoughts and prioritizing their news on attack and crimes. Publication of negative news ultimately hampered the journalist. Standardization of newspaper in the changing context can be achieved by promoting more creative works and encouraging those activities which have reformed the society and also contributed to bring sound development. The society never can go up just reading negative news and anti social news. The journalist needs to reform their vision. They should focus good, encouraging and creative news rather than publishing critical news on harassment to personalities and cool events. Weekly newspaper are playing active role as mouthpiece of their parties and/or school of thoughts. They are neglecting people's aspiration and highlighting one sided thoughts without considering other's ideas and visions. This brought high toll in vandalism in media. Crime is increasing. The value system has been collapsed. People discouraged and country headed towards failure state. Newspaper should work as a watching dog to protect human values, national sovereignty, national unity and identity. Creativity and constructive ideas must be promoted. Narrow and selfish individual never can be a successful journalist. A journalist is also a lawyer and referee. Journalist can play a role of parents to the nation. Freedom for the enrichment of human civilization must be considered. A journalist has great role but never can be a dictator. Journalist is a mediator not ruler. Journalist can make the king not treat himself as a king. Journalist is freedom fighter but restricted to use own freedom. Social norms and values, academic conscience and humanistic attitude control them. To promote society, journalist should encourage literature, music and art. Without enriching them, man becomes beast. To promote development, journalist has to cooperate to disseminate new creative and constructive ideas. Too much criticism is fatal. It may boomerang. Critical thinking is essential but it should be for the betterment of situation not to bring worst condition in the life of the people and country. In my observation, maturity is lacking in the contemporary Nepali newspaper. The situation will improve soon because young journalist is emerging and they are in learning process. Their learning certainly will teach to guide the betterment of the society and bring fruitful development in the nation. DOI: http://dx.doi.org/10.3126/ttp.v5i0.1949 The Third Pole, Vol. 5-7, PP 1-27:2007